The impacts of vitamin D supplementation on serum levels of thyroid autoantibodies in patients with autoimmune thyroid disease: a meta-analysis - Luo,Dongdong; Li,Bojuan; Shan,Zhongyan; Teng,Weiping; Liu,Qigui; Li,Jing (PeerJ, 2025)
Background Although vitamin D (VitD) deficiency had been found with close relationship with autoimmune thyroid disorders (AITD), the findings about the impacts of VitD supplementation on the production of anti-thyroid peroxidase (TPOAb) and anti-thyroglobulin antibodies (TgAb) remained inconsistent. Thus, a systemic meta-analysis was conducted to figure out the exact effects of VitD intervention on the production of TPOAb and TgAb in AITD patients. Methods We searched PubMed, Web of Science, Embase and The Cochrane Library databases for all clinical studies up to May 2023, which evaluated the changes in serum TPOAb and TgAb titers of AITD patients after VitD intervention. In addition, three subgroup analyses were carried out based on the duration of vitamin D supplementation, the initial nutritional status of participants, and the frequency of vitamin D administration. Results A total of 10 cohorts from 10 clinical trials with 577 patients with AITD were included. The serum titers of TPOAb and TgAb were significantly decreased after VitD supplementation as compared with their pre-treatment levels, respectively. However, a significant post-treatment reduction of serum TPOAb level was found only in the AITD patients with initial VitD insufficiency/deficiency, while an obvious decrease of serum TgAb was shown if only those studies without consideration of the pre-treatment VitD status were included. Serum TPOAb and TgAb titers were significantly decreased in the patients receiving VitD supplementation for at least 3 months, but not in the ones for less than 3 months. Serum titers of TPOAb and TgAb were both pronouncedly reduced in the patients receiving daily administration of VitD rather than weekly regimen. This study provides new evidence for the potential role of vitamin D supplementation in the treatment of AITD. Conclusions AITD patients may benefit with the reduction of TPOAb and TgAb production after a VitD supplementation (2800–60000 IU/week) for at least 3 months, especially with a decrease of serum TPOAb level when initially VitD insufficient/deficient, which mechanisms await further investigation. Systematic Review Registration PROSPERO, identifier CRD42023424029.
Keywords: Vitamin D; Autoimmune thyroid disorder; Anti-thyroid peroxidase antibody; Anti-thyroglobulin antibody; Meta-analysis